2016
DOI: 10.1002/adma.201601859
|View full text |Cite
|
Sign up to set email alerts
|

Superior Piezoelectric Properties in Potassium–Sodium Niobate Lead‐Free Ceramics

Abstract: A superior piezoelectric coefficient (d = 570 ± 10 pC N ), the highest value reported to date in potassium-sodium niobate-based ceramics, is obtained in (1-x-y)K Na Nb Sb O BaZrO - Bi K HfO ceramics. This high d value can be ascribed to the co-existence of "nano-scale strain domains" (1-2 nm) and a high density of ferroelectric domain boundaries. Therefore, ternary KNN-based ceramics demonstrate the potential for applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
333
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 635 publications
(349 citation statements)
references
References 29 publications
9
333
0
Order By: Relevance
“…As shown in Figure 17, an in vitro intravascular ultrasound (IVUS) image of a human cadaver coronary artery was obtained by such a lead-free transducer with adequate resolution and contrast to differentiate the vessel wall and fibrous plaque. Various studies have also shown potential applications of such BaTiO3-based lead-free ceramics, ranging from energy harvesting to energy storage, which can provide guidelines for the next generation of Pb-free materials with even better piezoelectric properties, for example in high TC KNN based piezoceramics [18,91,92]. …”
Section: Applications and Outlinementioning
confidence: 99%
“…As shown in Figure 17, an in vitro intravascular ultrasound (IVUS) image of a human cadaver coronary artery was obtained by such a lead-free transducer with adequate resolution and contrast to differentiate the vessel wall and fibrous plaque. Various studies have also shown potential applications of such BaTiO3-based lead-free ceramics, ranging from energy harvesting to energy storage, which can provide guidelines for the next generation of Pb-free materials with even better piezoelectric properties, for example in high TC KNN based piezoceramics [18,91,92]. …”
Section: Applications and Outlinementioning
confidence: 99%
“…Then in 2014, the breakthrough in piezoelectricity (d 33 $ 490 pC/N) was made in (1 À xÞ(K 1Ày Na y Þ(Nb 1Àz Sb z ÞO 3 -xBi 0:5 (Na 1Àw K w Þ 0:5 ZrO 3 system through normal sintering method. Through optimizing the composition of designed KNN system, the R-T phase boundary was constructed and a good comprehensive 87 At the same year, a new material system comprising (1 À x À yÞK 1Àw Na w Nb 1Àz Sb z O 3 -xBiFeO 3 -yBi 0:5 Na 0:5 ZrO 3 was designed to attain a high d 33 of 550 pC/N and a high T C of 237 ○ C through constructing an R-T phase boundary. 88 This work presents the good comprehensive performance of d 33 and T C , which is superior to those of reported KNN-based ceramics regardless of phase boundary types.…”
Section: R-t Phase Boundariesmentioning
confidence: 99%
“…[1] Particularly, the construction of new phase boundary by simultaneously shifting the rhombohedral-orthorhombic and orthorhombic-tetragonal phase transition temperature (e.g., T R-O and T O-T ) toward room temperature proved to enhance the piezoelectric properties of KNN-based ceramics. [1,7] Although the improved piezoelectricity can be guaranteed by means of phase boundaries, the related electrical properties still exhibited the strong temperature dependence due to the nature of polymorphic phase boundary that is different from the morphotropic phase boundary in PZT-based ceramics. [1,2,4,5] More importantly, the systematical investigations on how the phase boundaries affected the strain and its temperature stability is still missing, which could further promote the understanding of KNNbased ceramics.…”
mentioning
confidence: 99%